2023
DOI: 10.1039/d2sc05463a
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific interactions between Cas12a and dsDNA located downstream of the PAM mediate target search and assist AsCas12a for DNA cleavage

Abstract: Cas12a is one of the most commonly-used Cas proteins for genome editing and gene regulation. The first key step for Cas12a to fulfill its function is to search for its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…Therefore, the update or assembly of Cas protein is also an efficient way to optimize the detection system. The update of the Cas protein may be achieved by rational design 122 or directed evolution. 123 Besides changing the protein, integrating Cas proteins of different types could improve the detection efficiency, too.…”
Section: ■ Future Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the update or assembly of Cas protein is also an efficient way to optimize the detection system. The update of the Cas protein may be achieved by rational design 122 or directed evolution. 123 Besides changing the protein, integrating Cas proteins of different types could improve the detection efficiency, too.…”
Section: ■ Future Outlookmentioning
confidence: 99%
“…For instance, recently, Sun et al revealed that a highly conserved positive-charge-enriched α helix in the Cas12a protein played a significant role in target searching and cleavage efficiency, and the target specificity can be modulated by engineering its residues, too. Through finding a key domain in Cas12a for target searching, this discovery pointed out a new strategy for Cas protein engineering, which may improve its specificity by a large margin . Studies on the mechanism could help us design the biosensor more efficiently and rationally, and more studies should be made on this aspect.…”
Section: Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cas12a can process precursor crRNA (pre-crRNA) into mature crRNA, 16 which will obtain multiple crRNAs in one transcript simultaneously, achieving labeling multiple loci of the same target or different targets. Moreover, previous reports have demonstrated that PAM is also necessary for CRISPR/Cas12a during the target searching process, 17,18 analogous to CRISPR/ Cas9. Thus, we envisioned that the CRISPR/Cas12a system may possess more advantages for engineering an RNA imaging platform in live cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These results verified the fact that the introduction of PAMmer(ACTB) is helpful to search for ACTB mRNA, consistent with the previous report of Cas12a/crRNA for asymmetrically searching the target flanking the PAM site. 17 In addition to the initial PAM recognition, the ability of specific recognition of the CRISPR/Cas12a system for the target is strongly influenced by the complementarity between the target and the seed region in crRNA. 25 To study the effect of mismatching in the seed region on RNA recognition by our proposed system, we designed a series of artificial crRNA sequences bearing one, two, and three nucleotide mismatches (m1, m2, m3) close to the first five bases of PAM in the seed region using a commonly overexpressed HER2 mRNA in breast cancer as a model 30 (Figure S6A).…”
Section: ■ Introductionmentioning
confidence: 99%